2018
DOI: 10.3389/fpubh.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-Treated Nets Utilization and Associated Factors among under-5 Years Old Children in Mirab-Abaya District, Gamo-Gofa Zone, Ethiopia

Abstract: BackgroundMalaria can be prevented using cost-effective interventions. It can be prevented at large via the use of insecticide-treated mosquito nets (ITNs). The use of ITNs decreases malaria mortality rates by 55% in under-5 years old children in Africa, Ethiopia, realizing the effectiveness, scaling up distribution and utilization of ITNs to cover 100% of children less than 5 years of age. However, little is known about ITNs utilization and factors associated with the utilization in under-5 years old children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 14 publications
12
40
0
Order By: Relevance
“…The likelihood of ITN use was higher in smaller households compared to larger households in most countries excluding Burundi and Zimbabwe. This finding concurs with those of recent reviews and analyses of ITN use in African countries including Zambia, and Zimbabwe [7][8][9][10], in which the odds of ITN use decreased with larger households, with five or six members compared to those with less than five household members. In terms of the number of children, the results showed that the use of ITNs in households with more than one child under 5 was significantly higher compared to those households with only one child.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The likelihood of ITN use was higher in smaller households compared to larger households in most countries excluding Burundi and Zimbabwe. This finding concurs with those of recent reviews and analyses of ITN use in African countries including Zambia, and Zimbabwe [7][8][9][10], in which the odds of ITN use decreased with larger households, with five or six members compared to those with less than five household members. In terms of the number of children, the results showed that the use of ITNs in households with more than one child under 5 was significantly higher compared to those households with only one child.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies attempted to assess the socio-economic factors associated with ITNs use in several African countries found that factors that have been identified to increase the likelihood of ITNs use among households living with at least a child under 5 included: small-size households with equal or less than four household members [7][8][9][10], urban residents [11][12][13], living in improved housing [14], wealthier households, and households with short distance to retail stores [15]. Moreover, high level of education has been linked to appropriate ITNs use [10][11][12][13][16][17][18].…”
mentioning
confidence: 99%
“…29 In contrast, a study which conducted in Gamo-Gofa zone, Ethiopia identified that only 37.2% of children under 5 years of age utilized ITNs at a night time. 30 Since our study is a cross sectional study and without evidence of follow-up observation, the interpretation of results is limited concerning the utilization of ITNs by households. However, the result showed the significance of ITNs agreeing with the percentage of ITNs use by households.…”
Section: Discussionmentioning
confidence: 95%
“…to receive an RDT test-it is an opportunity to reinforce health behaviours like net use-this is why it is good to use every opportunity of an encounter with the health service to reinforce positive health behaviours-as sustaining these behaviours is critical for malaria control. The number of household members is another factor influencing use of mosquito nets [29,30]. Women from households with less than 5 members were more likely to use mosquito nets than those whose household members were 5 or more.…”
Section: Discussionmentioning
confidence: 99%